2009
DOI: 10.1038/nature08529
|View full text |Cite
|
Sign up to set email alerts
|

Uptake through glycoprotein 2 of FimH+ bacteria by M cells initiates mucosal immune response

Abstract: The mucosal immune system forms the largest part of the entire immune system, containing about three-quarters of all lymphocytes and producing grams of secretory IgA daily to protect the mucosal surface from pathogens. To evoke the mucosal immune response, antigens on the mucosal surface must be transported across the epithelial barrier into organized lymphoid structures such as Peyer's patches. This function, called antigen transcytosis, is mediated by specialized epithelial M cells. The molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
551
4
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 560 publications
(601 citation statements)
references
References 38 publications
14
551
4
12
Order By: Relevance
“…The colonic ILFs in RANKL Ϫ/Ϫ mice included some mature ILFs covered by a FAE, demonstrating that the full spectrum of ILF development can be completed in the colon in the absence of RANKL. However, M cells, as identified by their expression of the M cell-specific marker GP2, 20 were present in the FAE overlaying colonic ILFs in RANKL ϩ/Ϫ mice, but not in RANKL Ϫ/Ϫ mice ( Figure 4D). We previously showed that differentiation of M cells in the PP FAE requires RANKL.…”
Section: Rankl ϫ/ϫ Mice Develop Colonic Aggregates That Include B-celmentioning
confidence: 99%
“…The colonic ILFs in RANKL Ϫ/Ϫ mice included some mature ILFs covered by a FAE, demonstrating that the full spectrum of ILF development can be completed in the colon in the absence of RANKL. However, M cells, as identified by their expression of the M cell-specific marker GP2, 20 were present in the FAE overlaying colonic ILFs in RANKL ϩ/Ϫ mice, but not in RANKL Ϫ/Ϫ mice ( Figure 4D). We previously showed that differentiation of M cells in the PP FAE requires RANKL.…”
Section: Rankl ϫ/ϫ Mice Develop Colonic Aggregates That Include B-celmentioning
confidence: 99%
“…The seminal paper of Hase et al demonstrated GP2 to be involved in the generation of humoral immune responses to molecules of the intestinal content interacting specifically with GP2 on M cells [55]. These findings have led to a better understanding of autoimmunity against GP2 in CrD-specific inflammation and to a dramatic change in the understanding of the physiology of GP2.…”
Section: Glycoprotein 2 and The Link To Intestinal Inflammationmentioning
confidence: 99%
“…Defective THP synthesis is associated with an elevated susceptibility of mice to urinary tract infections [69]. In this context, the elegant study by Hase et al demonstrated that GP2 selectively binds to a subset of commensal and pathogenic enterobacteria, including E. coli and Salmonella enterica serovar Typhimurium [55]. Akin to THP, this type of binding is mediated by FimH of type I pili on the bacterial outer membrane [70].…”
Section: Physiological Role Of Glycoproteinmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-aggregating, non-digestive autoantigenic GP2 is secreted along with digestive proenzymes and represents a major pancreatic plug component [4,16,[26][27][28]. GP2 does not appear to play a decisive intracellular role during secretion but rather an antimicrobial and immunomodulating one after its release into the intestine despite its reported regulation of acinar endocytosis or ZG assembly [29][30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%